If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 38x + 40 = 12 Reorder the terms: 40 + 38x = 12 Solving 40 + 38x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 38x = 12 + -40 Combine like terms: 40 + -40 = 0 0 + 38x = 12 + -40 38x = 12 + -40 Combine like terms: 12 + -40 = -28 38x = -28 Divide each side by '38'. x = -0.7368421053 Simplifying x = -0.7368421053
| (M-n+k)(m+7n-7k)=0 | | 4x+2y=160 | | 93.63=4.7p+8.7p-2.6p | | 634=x^2 | | 16/15= | | y+6=55 | | 6+4(s+3t)= | | 99-n=66 | | 28+z=123 | | 1076=x^2 | | 59+y=104 | | y=-10+-8x+2x^2 | | a-47=29 | | 6x+13-3x-7= | | 228=12x | | y=2x^2-8x-10 | | y-16+15=60 | | 36-2=-45 | | 2.8+2.2+x=0 | | 4.7+10m=6.98 | | 10x+15+13x+26x=180 | | 13x+7=39 | | 72/y-6=6 | | C=5x^2-200x+4000 | | 2+5+x=0 | | 3x^2+x=3.75 | | X^2-46x+225=0 | | 400=x^2 | | (x+15)(x+5)(10x-20)=180 | | t/5-4=13 | | 5.9x=-17.11 | | -2*(t-1)=3*(6t-6) |